Implications of Changes in Households and Living Arrangements for Future Home-Based Care Needs and Costs for Disabled Elders in China. (April 2015) - Zeng, Yi; Chen, Huashuai; Wang, Zhenglian; Land, Kenneth C.
Objectives: To better understand future home-based care needs and costs for disabled elders in China.Method: To further develop and apply the ProFamy extended cohort-component method and the most recent census and survey data.Results: (a) Chinese disabled elders and the annual growth rate of the percentage of national gross domestic product (GDP) devoted to home-based care costs for disabled elders will increase much more rapidly than the growth of total elderly population; (b) home-based care needs and costs for disabled oldest-old aged 80+ will increase much faster than that for disabled young-old aged 65-79 after 2030; (c) disabled unmarried elders living alone and their home-based care costs increase substantially faster than those disabled unmarried elders living with children; (d) percent of rural disabled oldest-old will be substantially higher than that of rural population after 2030; (e) sensitivity analyses show that possible changes in mortality and elderly disability status are the major direct factors affecting home-based care needs and costs; (f) caregivers resources under the universal two-child policy will be substantially better than that under the rigorous fertility policy unchanged.Discussion: We discuss policy recommendations concerning pathways to healthy aging with relatively reduced care costs, including reductions of the prevalence of disability, gender equality, the universal two-child policy and resources of caregivers, encouragements of rural-to-urban family migration and elder's residential proximity to their adult children, and remarriages of not-married elders.